Comparison of Stapled Hemorrhoidopexy With Traditional Excisional Surgery For Hemorrhoidal Disease: An Updated Systematic Review - Atep Lutpia Pahlepi; Ibrahim Risyad Pradana; Rostikawaty Azizah (International Medical Journal Corp. Ltd, 2025)
Background: Hemorrhoid patients encounter prolonged postoperative discomfort following conventional hemorrhoid surgery, resulting in delays in resuming work and daily routines. Stapled hemorrhoidopexy emerges as a novel approach, potentially enhancing pain management and recovery. This study aims to systematically review the comparison of stapled hemorrhoidopexy and conventional open hemorrhoidectomy in literatures of the last 5 years. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2019 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 1,099 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, four articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Stapled hemorrhoidopexy exhibited superior short-term outcomes compared to traditional hemorrhoidectomy. However, the traditional method had a lower recurrence rate compared to stapled hemorrhoidopexy.